Corruption as a Problem of Political Theory and Political Practice - Shashkova, A. V. (Vestnik MGIMO-Universiteta, 2015)
The present article is dedicated to the analysis of "corruption" from point of view of political practice and political theory. The present article studies historical examples of corruption: corruption during the era of Alexander the Great, Carthage, Roman Republic. The article gives the evolution of the term "corruption", pointing out current aspects of the term. The article provides positive and negative results of corruption, gives resume. The present article analyses corruption results: economical, political and social. Most important economical consequences of corruption are the following: increase of shadow economy, decrease of tax payments, weakening of the state budget, breach of market competition, decrease of market effectiveness, destabilization of the idea of market economy. Most important social consequences of corruption are the following: great distinction between the declared and real values, which creates a "double standard" of the moral and behavior, distraction of great sums from public and humanitarian development, increase of property disproportion, increase of social tension. The present article names most important political consequences of corruption: shift of ideas from public development to the security of power of oligarchy, decrease of trust to the state, decrease of image of the country at the international arena, increase of its economical and political isolation, decrease of political competition. The present article gives one of the resumes that the globalization process increases corruption. Together with globalization most important role is given to corporations and corporate corruption comes to the front raw.